Piqueteros: An experimental analysis of direct vs. indirect reciprocity (2015)
Research in behavioral economics has widely recognized the importance of reciprocity concerns in shaping individual behavior. The literature is however dominated by a focus on direct reciprocity. Motivated by a real life situation in Argentina - the Piqueteros (pickets) conflict - I designed a three-player three-stage game in order to investigate what type of reciprocity prevails in the face of a negative externality in an environment that allows for direct and indirect reciprocity simultaneously. I show that (negative) reciprocity from the directly affected second mover is more frequent than punishment from the indirectly affected third party. However, the third party more frequently punishes the first mover than the second mover, even though he is negatively affected by the latter's punishment effort while not by the former's move directly. In oder words, in real life settings featuring the incentives captured by this paper's experimental design, affected third parties more frequently act in line with indirect rather than direct reciprocity. © 2015, Walter de Gruyter GmbH. All rights reserved.